2019
DOI: 10.3390/jcm8101731
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Septic Shock—Defined by Updated Sepsis-3 Criteria in Critically Ill Patients

Abstract: Sepsis is commonly associated with acute kidney injury (AKI), particularly in those requiring dialysis (AKI-D). To date, Sepsis-3 criteria have not been applied to AKI-D patients. We investigated sepsis prevalence defined by Sepsis-3 criteria and evaluated the outcomes of septic-associated AKI-D among critically ill patients. Using the data collected from a prospective multi-center observational study, we applied the Sepsis-3 criteria to critically ill AKI-D patients treated in intensive care units (ICUs) in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
0
11
0
3
Order By: Relevance
“…Of note, the patients in the worst cluster (cluster 2) had the best renal function parameters, including higher baseline eGFR, lower BUN and SCr before initiating RRT, higher eGFR and bicarbonate level when weaning off RRT, as well as lower BUN and SCr at 24 h after weaning off RRT. These features have been associated with a good prognosis [ 17 , 26 , 32 ]. However, the patients in cluster 2 also had more severe illness in terms of higher qSOFA score and lower bicarbonate level before initiating RRT, which have been associated with a poor prognosis [ 26 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, the patients in the worst cluster (cluster 2) had the best renal function parameters, including higher baseline eGFR, lower BUN and SCr before initiating RRT, higher eGFR and bicarbonate level when weaning off RRT, as well as lower BUN and SCr at 24 h after weaning off RRT. These features have been associated with a good prognosis [ 17 , 26 , 32 ]. However, the patients in cluster 2 also had more severe illness in terms of higher qSOFA score and lower bicarbonate level before initiating RRT, which have been associated with a poor prognosis [ 26 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These features have been associated with a good prognosis [ 17 , 26 , 32 ]. However, the patients in cluster 2 also had more severe illness in terms of higher qSOFA score and lower bicarbonate level before initiating RRT, which have been associated with a poor prognosis [ 26 , 33 ]. The results showed that clustering analysis could cluster baseline characteristics with a temporal change in disease severity into distinct phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study showed that 3–5 h consecutive oliguria in patients with septic shock may be an indicator to measure the risk of AKI ( 13 ). Meanwhile, the most frequent indication for acute dialysis was oliguria ( 14 ). In general, whether patients are complicated with AKI and whether to undergo RRT or diuretic therapy are significantly related to UO theoretically.…”
Section: Discussionmentioning
confidence: 99%